TEACHING FOREIGN LANGUAGES IN THE SECONDARY AND HIGHER EDUCATIONAL ESTABLISHMENTS: OVERVIEW OF MAIN APPROACHES - Olga Komar (Pavlo Tychyna Uman State Pedagogical University, 2017)
Rapid social changes in different spheres determine new requirements to the graduates of the higher educational establishments. The article presents a whole complex of techniques that is aimed at developing not only language skills, but crea-tivity and general outlook of the students, that help to create an English-speaking environment in which they work, express their thoughts, draw conclusions. The article is devoted to the content analysis of basic approaches to English language teaching. The author compares traditional and innovative approaches, determines their benefits and drawbacks. Within the framework of this research the author dis-tinguished three basic approaches (methods) in teaching a foreign language: commu-nicative, intensive and linguoculturological. The characteristic principles of each of them are presented in the article. The author states that they focus on widening the world view, motivation level increase, creative initiative cultivation and effective communication performance. The conception of the research problem in the educa-tional sphere of the secondary and higher educational establishments has been theo-retically generalized. The point of the article is based on the fact that professional training of future foreign language teachers is a process of learning, understanding and specific knowledge, skills and proficiencies of future teachers who perform the functions of future professional activities, fulfill their functions in accordance with their professional duties. The scientific literature analysis results, concerning the approaches viewed, show advantages and disadvantages of each of them, so that they need some modifying and improvement, what will be the prospects for our further research in this direction.